Television news, infotainment and sensationalism: an analysis of Rede TV! - Costa, Heliany Rodrigues (2023)
This paper aims to analyze the National Alert program to understand how the spectacularization of news about crime interferes in the public’s relationship with conventional professional journalism. The study was concatenated in four parts: observation of the content and profile of viewers; public analysis based on opinion polls; interview with the presenter of the National Alert program; and the analysis of the construction of belonging based on Hall’s et al. (1980) coding-decoding model. It was concluded that the Programa Alerta Nacional brings with it several characteristic elements of political ideologization and influence on its viewers, based on a discourse that reflects an approach that denotes the perception of social behavior imbued with a process of humor based on the construction of the bond receptive communicational.